Mengapa Masyarakat Masih Enggan Dengan Bank Syariah? - Saiful Bahri (LPPM ISNJ Bengkalis, 2016)
There was a number cause why people prefer not to deal with sharia banking. Several though discover that sharia unbankable caused on several reasons. Between them assumed that sharia banking system and operational no so different from a conventional concept. Another cause was realized that the people applied and accessed the conventional system and product from earlier. By literature study methodology, this study to try to point out a solving of this problem. Finally, sharia bank could perform out of the box system, such as well as charity or philanthropy to realize Islamic economic value. Infak or shadaqah on various types known could make a positive impact for sharia banking.